2000
DOI: 10.1002/(sici)1099-1077(200003)15:2<113::aid-hup150>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A and beyond: the role of serotonin and its receptors in depression and the antidepressant response

Abstract: Since its discovery 50 years ago, the role of the indoleamine 5-HT (5-hydroxytryptamine; serotonin) in the pathogenesis of depression and in the mechanism of action of antidepressant drugs has been the subject of considerable research. Advances in molecular biology and radioligand techniques have led to the functional characterisation of at least 14 serotonin receptor subtypes. This classification has led to the development of selective compounds that have aided in the efforts of dissecting the complex role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(52 citation statements)
references
References 200 publications
(165 reference statements)
1
51
0
Order By: Relevance
“…More evidence that sustains the participation of 5-HT 1A receptors in the effect of serotonergic antidepressants results from the use of antagonists to the 5-HT 1A receptor subtype, such as pindolol (Artigas et al, 1994(Artigas et al, , 1996 and WAY 100635 (Davidson and Stamford, 1995;Dawson and Nguyen, 1998;Gundlah et al, 1997;Hjorth et al, 1997;Millan et al, 1998), which, by blocking presynaptic serotonergic receptors, can facilitate the antidepressant action of serotonergic compounds in both clinical and preclinical studies (for a review, see Cryan and Leonard, 2000).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…More evidence that sustains the participation of 5-HT 1A receptors in the effect of serotonergic antidepressants results from the use of antagonists to the 5-HT 1A receptor subtype, such as pindolol (Artigas et al, 1994(Artigas et al, , 1996 and WAY 100635 (Davidson and Stamford, 1995;Dawson and Nguyen, 1998;Gundlah et al, 1997;Hjorth et al, 1997;Millan et al, 1998), which, by blocking presynaptic serotonergic receptors, can facilitate the antidepressant action of serotonergic compounds in both clinical and preclinical studies (for a review, see Cryan and Leonard, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…For example, it is accepted that the 5-HT 1A , 5-HT 2 , and 5-HT 3 receptors all participate in the antidepressant-like action induced by selective serotonin re-uptake inhibitors (SSRIs) such as fluoxetine (FLX), paroxetine or sertraline (Blier, 2001;Blier and Ward, 2003;Duman et al, 1997;Li et al, 1996Li et al, , 1997aRupprecht et al, 2001;Stahl, 1998a). In particular, the 5-HT 1A receptor has been proposed as a target of antidepressants that exhibit a clear therapeutic effect (for reviews see Blier and Ward, 2003;Cryan and Leonard, 2000). In this sense, in vitro and in vivo studies have shown that several SSRIs promote a desensitization of the presynaptic 5-HT 1A receptor subtype (Blier, 2001;Le Poul et al, 1995;Li et al, 1996Li et al, , 1997a, and that facilitates a general enhancement of serotonin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of brain 5-HT neurotransmission has been shown to be intricately associated with complex psychiatric disorders, such as depression and anxiety disorders (Cryan and Leonard, 2000;Jones and Blackburn, 2002;Kiss, 2008;Law et al, 2007). Among the diverse 5-HT receptor subtypes known to date, interactions with metabotropic 5-HT 1A receptors seem to be most relevant for understanding the mechanisms of action of antidepressants, anxiolytics such as azapir-ones, and some atypical antipsychotics (Blier and Ward, 2003;Bockaert et al, 2006;Diaz-Mataix et al, 2005;Meltzer et al, 2003;Pucadyil et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the 5-HT 1A receptor (5-HT 1A R) is very susceptible to modulation by stress and HPA-axis activation and is well known to play an important role in the pathophysiology of mood disorders (Lopez et al, 1998;Cryan and Leonard, 2000;Leitch et al, 2003). Accumulating evidence points also to an important role for the neurotrophin brainderived neurotrophic factor (BDNF) in both the pathophysiology of mood disorders and in the therapeutic effects of antidepressants (Duman, 2002;Castren, 2004;Hashimoto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%